Correlation of Learning Media Types to Online Disinhibition Effects in Online Lectures - Mantara, Angga Yuni; Prastuti, Endang; Zahra, Gebi Angelina; Sebastian, Yhalza Syachna; Naibaho, Tini Sarah Yosephine (Jurnal Sains Psikologi, 2023)
The use of media affects how college students interact with lecturers, including the tendency of students to be more active in the learning process. The purpose of this research is to find out whether there is a relationship between the type of media and the online disinhibition effect in the online lecture process. Data were obtained from 616 respondents who filled out online questionnaires and used Kendall’s tau analysis to test the research questions. The results of the analysis showed that there was no significant relationship between the type of media and the level of online disinhibition effect (rτ equals .02, p equals .56). This is because the closeness of the interaction in the online class that occurs is able to match the interaction in the offline class and everyone in the class already knows each other, so that whatever media used is not related to the level of online disinhibition effect.